Stroke Outreach in an Inner City Market: A Platform for Identifying African American Males for Stroke Prevention Interventions - Sharrief, Anjail Zarinah; Johnson, Brenda; Urrutia, Victor Cruz (Frontiers in Neurology, 2015)
Abstract Background: There are significant racial disparities in stroke incidence and mortality. Health fairs and outreach programs can be used to increase stroke literacy, but they often fail to reach those at highest risk, including African American males. Methods: We conducted a stroke outreach and screening program at an inner city market in order to attract a high-risk group for a stroke education intervention. A modified Framingham risk tool was used to estimate stroke risk and a 10-item quiz was developed to assess stroke literacy among 80 participants. We report results of the demographic and stroke risk analyses and stroke knowledge assessment. Results: The program attracted a majority male (70%) and African American (95%) group of participants. Self-reported hypertension (57.5%), tobacco use (40%), and diabetes (23.8%) were prevalent. Knowledge of stroke warning signs, risk factors, and appropriate action to take for stroke symptoms was not poor when compared to the literature. Conclusions: Stroke outreach and screening in an inner city public market may be an effective way to target a high-risk population for stroke prevention interventions. Stroke risk among participants was high despite adequate stroke knowledge.